Evaluation of cytotoxic lymphocytes and their parasite strain specificity from African buffalo infected with Theileria parva - Baldwin, Cynthia L.; Malu, M.N.; Grootenhuis, J.G. (Wiley, 1988)
Summary Theileria parva‐reactive cytotoxic lymphocytes and their precursors were examined in the blood of African buffalo infected with T. parva and uninfected African buffalo. Peripheral blood mononuclear cells (PBM) from eight of 11 infected buffalo were found to have potent cytotoxic activity after stimulation with autologous parasitized cells for 6 days in vitro, while PBM from uninfected buffalo or PBM from infected buffalo not stimulated in vitro had no cytotoxic activity. The cytotoxic activity was specific for parasitized cells and genetically restricted since there was no killing on uninfected autologous lymphoblasts and a lower percentage of killing on parasitized allogeneic lymphocytes than on targets of autologous parasitized cells. The cytotoxic cells tested for parasite strain specificity were shown to kill autologous cells transformed with different stocks of both cattle‐derived (T. parva parva) and buffalo‐derived (T. parva lawrencei) parasites.